2021
DOI: 10.3390/foods10112611
|View full text |Cite
|
Sign up to set email alerts
|

Olive Tree Derivatives and Hydroxytyrosol: Their Potential Effects on Human Health and Its Use as Functional Ingredient in Meat

Abstract: Olive (Olea europaea) is one of the most extensive crops in the Mediterranean countries, and an important source of extra distinctive compounds that has been widely tested due to its known health benefits. Olive derivatives, such as extra virgin olive oil (EVOO) and olive leaves are rich in antioxidant compounds such as hydroxytyrosol (HXT) and oleuropein and oleic acid, as main monounsaturated fatty acid. Because of HXT molecular structure, its regular consumption reports important beneficial properties such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 61 publications
1
19
0
Order By: Relevance
“…Oblica . It is reported that hydroxytyrosol, due to its structure, has beneficial antioxidant, antimicrobial, anti-inflammatory, and anticancer properties [ 62 ]. The higher concentration of 3-hydroxytyrosol in cv.…”
Section: Discussionmentioning
confidence: 99%
“…Oblica . It is reported that hydroxytyrosol, due to its structure, has beneficial antioxidant, antimicrobial, anti-inflammatory, and anticancer properties [ 62 ]. The higher concentration of 3-hydroxytyrosol in cv.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to transfer a hydrogen from its phenolic OH groups to reactive oxygen species, minimizes the damage operated by oxidative processes implicated in the development of many diseases such as inflammation, cardiovascular diseases, diabetes, cancer and ageing [ 13 ] as well as oxidative deterioration in foodstuff [ 45 ]. While HT anti-cancerogenic and anti-diabetic effects have been already demonstrated [ 46 , 47 ] as well as its food preservative properties [ 48 ], in vivo studies have shown that HT supplementation inhibits the efflux of brain cell death markers, making this compound a potential neuroprotectant [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hydroxytyrosol has been proven to reduce oxidative markers such as ROS and malondialdehyde (MDA) and upregulate NO generation in vitro and in vivo [ 62 , 85 , 86 , 87 ]. The ortodiphenolic structure of HT is responsible for scavenging free radicals [ 28 ]. Serreli et al [ 88 ] reported conjugated metabolites of hydroxytyrosol and tyrosol-enhanced endothelial nitric oxide synthase (eNOS) expression and decreased superoxide production by activating AKT serine/threonine kinase 1 (AKT 1).…”
Section: Hydroxytyrosol In Oxidative Stress-induced Endothelial Dysfu...mentioning
confidence: 99%
“…Olive is a tree species with a history of 6000 years, as recorded by the International Olive Council (IOC). Around six million trees are cultivated around Mediterranean countries such as Spain and Greece [ 28 ] and further east to Islamic countries like Iran, Palestine, and Iraq [ 29 ]. Around 25 kg of olive leaves are obtained annually from pruning each tree [ 30 ].…”
Section: Introductionmentioning
confidence: 99%